PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA UNTUK MENINGKATKAN KUALITAS DAN KREATIVITAS GURU SMA NEGERI 1 LHOKSEUMAWE - Angga Pratama; Ilham Saputra; Hafizh Al Kautsar Aidilof; Muhammad Habib; Nasruddin Nasruddin (LPPM Universitas Al Muslim, 2022)
Advances in information technology are one of the potentials that are useful in improving learning methods. Currently, content and media that are directly related to science can be more interactive and interesting for students to trigger interest in learning. Internet technology can remove limitations in various information and provide learning materials more easily. However, there were still many teachers who focus on traditional and oral teaching approaches, even using less learning media. The use of learning media is very important for the teaching and learning process and the role of the media can be used in every discipline to enhance learning in the classroom and outside the classroom. The problems that have arisen so far indicate that teaching uses abstract concepts were not easy to be presented in both verbal and visual forms. Another goal was that visual media can be more easily understood and be easily accessed by students than text media. Therefore, another goal of this service was to train educators at SMA 1 Lhoksemawe to become more familiar with the latest learning media to be applied in the teaching and learning process. From the results of this communty service it is expected that teachers can use several multimedia in learning which is a combination of text, graphics, animation, images, video and audio which help students understand the material more easily.